ANALISIS STRATEGI PEMBELAJARAN GENETIKA DI SEKOLAH DASAR: TINJAUAN LITERATUR PADA METODE ANALOGI DAN ALAT PERAGA - Kania, Nala; Anggun Nur Andiany Wiyoso; Anisa Putri Mulyaningsih; Afrida Laily Alindra (Jurnal Citra Pendidikan, 2026)
Abstract (English) Genetics is one of the most challenging biology topics to teach at the elementary school level due to its abstract, microscopic nature and rich technical terminology, while students at that age are generally still at the concrete operational cognitive development stage. This article aims to identify the main conceptual challenges faced by elementary school students in learning genetics, analyze the effectiveness of various learning strategies that have been developed, and formulate evidence-based recommendations for the development of child-friendly genetics learning modules. This research uses a literature study approach with data sources in the form of national and international journal articles, textbooks, proceedings, and research reports published between 2016 and 2026. The results of the study indicate that the main obstacles in learning genetics include misconceptions about terminology, low intrinsic motivation of students, and a lack of varied teaching methods. Various learning interventions have proven effective in overcoming these obstacles, including the analogy method that acts as a cognitive bridge between abstract concepts and concrete understanding, the use of genetics button teaching aids that can increase learning completion by up to 100%, and digital gamification that produces high gain scores while reducing student learning anxiety. The literature synthesis confirms that no single method is sufficient, so the development of effective genetics modules requires an integrative approach that combines analogies, concrete teaching aids, and gamification elements within a systematic development framework such as the 4D and ASSURE models.